ANALYSIS OF THE GOVERNMENT AGENCY PERFORMANCE ACCOUNTABILITY REPORT (LAKIP) BASED ON THE REGULATION OF THE MINISTER OF STATE APPARATUS EMPOWERMENT AND BUREAUCRATIC REFORM OF THE REPUBLIC OF INDONESIA NUMBER 53 OF 2024 AT THE KUTAI KARTANEGARA YEAR 2022 - Meilisa, Noor Shiva Chovifah (JEA17: Jurnal Ekonomi Akuntansi, 2024)
The Government Agency Performance Accountability Report (LAKIP) is a form of accountability for the implementation of duties and functions to account for the success and failure of achieving the organization's mission in achieving the goals and objectives that have been set through periodic accountability tools. This study aims to determine and analyze the Government Agency Performance Accountability Report (LAKIP) based on the Regulation of the Minister of State Apparatus Empowerment and Reform. The purpose if this study is to find out and analyze the Government Agency Performance Accountability Report (LAKIP) based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 53 of 2014 at the Kutai Kartanegara Regency Youth and Sports Office. This analysis is carried out by the Comparative Method. A method that compares the format of the Government Agency Performance Accountability Report (LAKIP) with the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 53 of 2014. The results of research conducted at the Youth and Sports Service show that the Kutai Kartanegara Regency Youth and Sports Service is in accordance with the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 53 of 2014. However, there is still one element that has not been fulfilled, in the Accountability section Performance in Accountability Organizational Performance Achievements are found in the comparison between targets and actual performance this year which are not in accordance with the Regulation of the Minister for Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 53 of 2014 and the organizational strategy targets in the value of performance accountability are not significant.